2017
DOI: 10.1038/jhg.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the proteolytic domain of LONP1 causes atypical CODAS syndrome

Abstract: Cerebral, ocular, dental, auricular, skeletal (CODAS) syndrome is a rare autosomal recessive multisystem disorder caused by mutations in LONP1. It is characterized by intellectual disability, cataracts, delayed tooth eruption, malformed auricles and skeletal abnormalities. We performed whole-exome sequencing on a 12-year-old Japanese male with severe intellectual disability, congenital bilateral cataracts, spasticity, hypotonia with motor regression and progressive cerebellar atrophy with hyperintensity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Conversely, het mice appear healthy, and we did not detect any gross phenotypic, nor histological alterations which could suggest the presence of inflammatory status or functional alterations of muscles, bones, nervous system and digestive tract. This is in agreement with previous studies performed on another Lonp wt/− mouse model [32,42] and with that observed in the parents of CODAS-affected patients, who appear healthy and without relevant phenotypic alterations, despite the mutation in one copy of LONP1 [36,39,45].…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, het mice appear healthy, and we did not detect any gross phenotypic, nor histological alterations which could suggest the presence of inflammatory status or functional alterations of muscles, bones, nervous system and digestive tract. This is in agreement with previous studies performed on another Lonp wt/− mouse model [32,42] and with that observed in the parents of CODAS-affected patients, who appear healthy and without relevant phenotypic alterations, despite the mutation in one copy of LONP1 [36,39,45].…”
Section: Discussionsupporting
confidence: 93%
“…To date, there are a few case reports of a LONP1 manifesting with a mitochondrial disease phenotype (5, 8). Other reports of recessively inherited variants in LONP1 have been described in relation to CODAS syndrome (6, 7, 9), which could be distinguished from classical mitochondrial diseases by its distinctive clinical anomalies. However, patients with CODAS manifest with a varying clinical spectrum that may mimic that of a classical mitochondrial disease, including but not limited to, short stature, ptosis, hypotonia, and intellectual disability (6, 7, 26).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a group from Japan identified a compound heterozygous variant in LONP1 on whole exome sequencing in a 12-year-old male with atypical CODAS (9). His manifestations included severe intellectual disability, congenital bilateral cataracts, spasticity, hypotonia, motor regression, and progressive cerebellar atrophy with hyperintensity of the cerebellar cortex on MRI (9). Muscle biopsy was not performed; therefore, it is unclear if this case represented a LONP1 -related mitochondrial cytopathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are skeletal and dental anomalies that are pathognomonic for CODAS syndrome. Recently, one individual presenting atypical CODAS syndrome with myopathy resembling Marinesco–Sjögren syndrome was described ( 20 ). Furthermore, a c.2014C > T, p.(Arg627Cys) LONP1 variant has also been implicated in causing both CODAS syndrome and isolated paediatric cataracts ( 21 ).…”
Section: Discussionmentioning
confidence: 99%